2015
DOI: 10.1017/s0950268815001223
|View full text |Cite|
|
Sign up to set email alerts
|

Predicting the characteristics of the aetiological agent for Kawasaki disease from other paediatric infectious diseases in Japan

Abstract: SUMMARYAlthough Kawasaki disease (KD), which was first reported in the 1960s, is assumed to be infectious, its aetiological agent(s) remains unknown. We compared the geographical distribution of the force of infection and the super-annual periodicity of KD and seven other paediatric infectious diseases in Japan. The geographical distribution of the force of infection, which was estimated as the inverse of the mean patient age, was similar in KD and other paediatric viral infections. This similarity was due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 39 publications
2
32
0
Order By: Relevance
“…Furthermore, it was mathematically predicted that the infectious etiological agent of KD would be relatively common [34], based upon the young mean age of KD patients in Japan [36]. Consistent with this line of thought, TTVs are highly prevalent among healthy adult individuals [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it was mathematically predicted that the infectious etiological agent of KD would be relatively common [34], based upon the young mean age of KD patients in Japan [36]. Consistent with this line of thought, TTVs are highly prevalent among healthy adult individuals [37].…”
Section: Discussionmentioning
confidence: 99%
“…This pantrophic characteristic of TTV7 is consistent with the intestinal and respiratory symptoms that are prodromal to KD. Previous epidemiological studies predicted that at least one of the etiological agent(s) for KD would be capable of persistent infection [33, 34]. Notably, persistent infection is a characteristic reported to be shared by the anelloviruses [35].…”
Section: Discussionmentioning
confidence: 99%
“…Cases are rarely seen below 6 months of age which could be attributed to the passive transmission of maternal immunoglobulins providing protection to the child at an early age, which gradually decreases over the time [37]. Recently, Nagao et al also reported that KD has a similar mode of transmission to infections upon close contact with infected persons [38]. …”
Section: Etiopathogenesismentioning
confidence: 99%
“…These inflammatory processes could be produced only in response to either intrinsically autoimmune reactions or extrinsically inhaled particles, or as a result of infections. A recent study postulated that KD is similar to other pediatric viral infections and suggested a long‐term persistence in the host, as for Exanthema subitum . However, this assumption would imply long incubation times and lifelong persistence and, therefore, a large pool of asymptomatic infections, which has been disregarded on the basis of detailed studies of KD population epidemiology in Japanese prefectures …”
Section: Is Kd An Infectious Disease? Lessons From Kd Epidemiologymentioning
confidence: 99%
“…A recent study postulated that KD is similar to other pediatric viral infections and suggested a long-term persistence in the host, as for Exanthema subitum. 33 However, this assumption would imply long incubation times and lifelong persistence and, therefore, a large pool of asymptomatic infections, which has been disregarded on the basis of detailed studies of KD population epidemiology in Japanese prefectures. 34 In the present study, person-to-person spread of an infection was examined to determine if such an etiological agent could fit the observed data.…”
Section: Is Kd An Infectious Disease? Lessons From Kd Epidemiologymentioning
confidence: 99%